(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article is mainly about the artistic interpretation of plot structure in short stories of Shukur Kholmirzayev. Extracts from his short stories are given in order to support with explanations and examples as well.